PROVISION OF EFFECTIVE EDUCATIONAL PROCESS BASED ON STANDARDIZING E-TESTS MEANS - Tatyana V. Krupa; Pavel E. Ovchinnikov; Yulia A. Severina; Olga A. Shalyapina; Elena V. Rybalko (Открытое образование (Москва))
Some issues on increasing education process efficiency as a result of usage of developed system of training electronic tests are considered. Some problems of standardization of educational tests are discussed. A particular technique of effective training tests development is shown, followed by analysis of the results of applying the training tests in the educational process, focused on small groups of students.